230k views
3 votes
How do i solve this?

How do i solve this?-example-1

2 Answers

2 votes
Subtract 6 from both sides
6+ k/3 -6 = 33-6
K/3 = 27
Multiply both sides by three
K/3 * 3 = 27 * 3
K = 81
User Squeegee
by
4.9k points
2 votes

Answer:

k = 81

Explanation:

6 +
(k)/(3) = 33 ( subtract 6 from both sides )


(k)/(3) = 27 ( multiply both sides by 3 to clear the fraction )

k = 3 × 27 = 81

User Ihkawiss
by
5.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.